Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.